Tales from the dirt: Post-anthropocentric perspectives on Brazil's past. (October 2022) - de Carvalho Cabral, Diogo; Vital, André Vasques; Lopes, Gabriel
Abstract: The article proposes a novel approach to Brazil's history by radicalising environmental history's call for writing biophysical environments into the human past. We offer three independent narrative experiments centring nonhuman organisms and things and their power to shape human lives, institutions, and documents. Focusing on ants, mosquitoes, and plankton, these stories put Brazil's early modernity (1850–1950) into perspective, highlighting the immersion of humans in a wider world of agentic beings and things. Our approach emphasizes the uniqueness of individual experiences engendered by the randomness and contingency of a multitude of unexpected encounters with other-than-human entities. We conclude by tracing the broad outlines of a historical approach capable of narrating and explaining Brazil as a more-than-human political community. Highlights: Offers a post-anthropocentric approach to Brazil's environmental history. Explores how nonhuman beings co-produced documents, landscapes, and biographies. Shows how ants could express themselves through self-narratives. Shows how mosquitoes shaped entomological eradication campaigns. Shows how plankton played a role in institutional human politics.